Rainfall Analysis for Ensuring Soil Moisture Availability at Dryland Areas of Semi-Arid Indore Region of Madhya Pradesh - A.S. TOMAR (Journal of Soil and Water Conservation, 2022)
The most important limiting factor for producing crops in dry farming areas is limited availability of soil moisture due to uneven distribution and erratic nature of rainfall. The long-term rainfall data analysis reveals that semi-arid Indore region of Madhya Pradesh receives 90.70% of average annual rainfall (954.25 mm) during S-W monsoon(June-September) with percentage deviation in the range of (-) 78.76% to (+) 99.39%. It was found that the months of July and August contributed 23.44% and 28.70% to its total expected value at 75%probability level of rainfall occurrence, considered as depend able rainfall for cultivating crops. This valuable information can be utilized for better crop planning, good drainage management, economical and optimum design of hydraulic structures and development of required irrigation plans for supplementing irrigation needs of crops commonly grown in and around semi-and dryland areas of Indore region of Madhya Pradesh.